BIAYA TRANSAKSI PADA SISTEM AGRIBISNIS DAN PENGARUHNYA TERHADAP PENDAPATAN USAHATANI UBI KAYU - Dwi Haryono; Zulkarnain zulkarnain; Wan Abbas Zakaria; Ktut Murniati; Rakhmiati Rakhmiati; Etik Puji Handayani; Fikri Syahputra; Vitratin Vitratin (Jurnal Penelitian Pertanian Terapan, 2021)
The objectives of the study are to analyze the amount of transaction cost on cassava agribusiness system and analyze the effect of transaction cost to the income of cassava farming in Central Lampung Regency. The research was held in the district of Rumbia, Central Lampung Regency. The reasearch used survey method to 141 cassava farmers in the district of Rumbia, Central Lampung Regency, taken purposively. The analysis used quantitative analysis method on Transaction cost (TrC); income analysis, and double linear regression. The results showed (1) transaction cost on cassava agribusiness system is Rp. 732.725,17/ha/farmer/season (2) the income of cassava farming is Rp. 10.666.036,03/ha means that cassava farming is worthed to be continuesly developed in Central Lampung Regency and transaction cost gave the real impact to the income of cassava farming